Necesidad de derogar el artículo 7 del código de la niñez y la adolescencia, respecto a la pensión de alimentos en caso en que el alimentado y el obligado, convivan bajo el mismo techo. - Mancheno Correa, Greis Paulina (2017)
One of the major problems affecting the public at large is the high cost of living, which leads to multiple charges within families, that difficulty can be covered, but not all, considering also that there is a high deficit poverty, unemployment, and general economic problems. In this context, the demand for food, especially the form of the mothers to parents has risen, families have separated or single mothers who request payment judicially food. In our society it has been observed that many mothers still living under the same roof as the parent, have been taken as an economical alternative, order alimony for their children, as permitted by the Code for Children and Adolescents. So it is necessary to protect the interests of families especially parents, as they are traditionally in charge of the maintenance of the family, so that's an unfair situation because obviously live under the same roof incur costs general for the whole family, undoubtedly it meets its obligations, so it is necessary to reform the Code of Children and Adolescents. That is why I intend reform as unnumbered article 7 of the Code for Children and Adolescents, so as to guarantee the rights of the father and foster conviviality and development, seeking the good life, as mandated by the Constitution of the Republic. Consider that alimony should not be misconceived or misused, the mere fact of living under the same roof, it requires obligors to contribute financially to his family, so this is contrary, rights, principles and guarantees enshrined in the Constitution.